ANALYSIS OF FORD COMPANY FINANCIAL RATIO PERFORMANCE BEFORE AND AFTER GLOBAL FINANCIAL CRISIS 2008 - Astina, Chandra Aditya (Universitas Sam Ratulangi, 2013)
Most countries around the globe were hit by economic crisis and caused many companies turned to bankruptcy in 2008. Many way the company try giving the best performance for not get the fail result, they shown the best in the bets result on the public, but not all company they are show the report financial, cause they no want the information will be know by other company, they think it is a rivalry in every company. The purpose of this research is to examine financial ratio performance of Ford is better, before and after global financial crisis 2008. Theories supporting research are financial management, financial statement, and financial ratio. Population is the annual report from 2002 to 2011 with sample of three years before and three years after 2008 and data will be analyzed using paired sample t-test. Result and conclusion is there is significant of Ford’s financial ratio performance before and after global financial crisis 2008. Keywords: financial management, financial ratio